A rare reason for the end of a career in competitive tennis - Trieb, K.; Huber, W.; Kainberger, F. (The Journal of Sports Medicine and Physical Fitness, 2008)
Stress fractures are reported in adolescents taking part in high standard sports and they are associated with specific sites for stress fractures. The first rib is also affected in rowers and ball throwing sports. This report describes the complications of such a case in a competitive tennis player at international level practicing 5 times a week with far-reaching consequences. Due to constant load dependent pain in the region of the right shoulder, standard diagnosis, X-ray, magnetic resonance imaging (MRI) and a computed tomography (CT) scan with 3-D reconstruction were done, showing a pseudoarthrosis of the first rib. Therefore, further treatment was conservative without pain relieve. At follow-up 5 years after onset of symptoms the patient did not play tennis, he did not complain pain, but control imaging still showed a pseudoarthrosis of the first rib. Our case shows that it is important, when treating shoulder pain in the overhead athlete, to think of the possibility of a stress fracture.